Urgensi Peran Orang Tua Membangun Kepemimpinan Anak di Era Disrupsi Teknologi Berdasarkan Ulangan 6: 6-9 - Santosa Santosa (EDULEAD: Journal of Christian Education and Leadership, 2021)
Technological disruption has an impact on fundamental changes in the order of human life. The disruption of technology has a positive and negative impact on human life. Facing the change and the impact of the technological disruption, the role of parents is very important in shaping leadership in children. This research was conducted by studying literature and text analysis of the Book of Deuteronomy 6:6-9. The results of this study aim to describe the urgency of the role of parents in building children's leadership according to Deuteronomy 6:6-9 in an era of technological disruption. The conclusion is the urgency of the role of parents in building children's leadership in an era of technological disruption according to Deuteronomy 6:6-9, among others: 1) To become spiritual educators of children. 2) Become a role model for spiritual discipline. 3) Discipline the spiritual growth of children. 4) Improve the relationship with children. 5) Give children responsibility for their spiritual growth. 6) Become a role model in healthy social media.AbstrakDisrupsi teknologi berdampak terhadap perubahan tatanan kehidupan manusia secara fundamental. Disrupsi teknologi memberi dampak positif dan negatif bagi kehidupan manusia. Menghadapi perubahan dan dampak akibat disrupsi teknologi, peran orang tua sangat penting dalam membentuk kepemimpinan dalam diri anak. Penelitian ini dilakukan dengan studi literatur dan analisis teks Kitab Ulangan 6: 6-9. Hasil penelitian ini bertujuan mendiskripsikan urgensi peran orang tua membangun kepemimpinan anak menurut Kitab Ulangan 6: 6-9 di era disrupsi teknologi. Diperoleh kesimpulan urgensi peran orang tua membangun kepemimpinan anak di era disrupsi teknologi menurut Ulangan 6: 6-9 antara lain: 1) Menjadi pendidik rohani Anak. 2) Menjadi role model disiplin rohani. 3) Mendisiplin pertumbuhan rohani anak. 4) Meningkatkan relasional dengan anak. 5) Memberi tanggungjawab anak terhadap pertumbuhan rohaninya. 6) Menjadi role model bermedia sosial sehat.